(untitled) (Eurasian Scientific Herald, 2022)
We present a numerical method for the Kuramoto-Sivashinsky equation with corresponding initial and boundary conditions. The exponential time differencing Runge-Kutta 4 method is used to solve the diagonal example of the KuramotoSivashinsky equation.